Impact of Polystyrene Microplastics on Soil Properties, Microbial Diversity and Solanum lycopersicum L. Growth in Meadow Soils - Shuming Liu; Yan Suo; Jinghuizi Wang; Binglin Chen; Kaili Wang; Xiaoyu Yang; Yaokun Zhu; Jiaxing Zhang; Mengchu Lu; Yunqing Liu (Plants)
The pervasive presence of microplastics (MPs) in agroecosystems poses a significant threat to soil health and plant growth. This study investigates the effects of varying concentrations and sizes of polystyrene microplastics (PS-MPs) on the Solanum lycopersicum L.’s height, dry weight, antioxidant enzyme activities, soil physicochemical properties, and rhizosphere microbial communities. The results showed that the PS0510 treatment significantly increased plant height (93.70 cm, +40.83%) and dry weight (2.98 g, +100%). Additionally, antioxidant enzyme activities improved across treatments for S. lycopersicum L. roots. Physicochemical analyses revealed enhanced soil organic matter and nutrient levels, including ammonium nitrogen, phosphorus, and effective potassium. Using 16S rRNA sequencing and molecular ecological network techniques, we found that PS-MPs altered the structure and function of the rhizosphere microbial community associated with S. lycopersicum L. The PS1005 treatment notably increased microbial diversity and displayed the most complex ecological network, while PS1010 led to reduced network complexity and more negative interactions. Linear discriminant analysis effect size (LEfSe) analysis identified biomarkers at various taxonomic levels, reflecting the impact of PS-MPs on microbial community structure. Mantel tests indicated positive correlations between microbial diversity and soil antioxidant enzyme activity, as well as relationships between soil physicochemical properties and enzyme activity. Predictions of gene function revealed that PS-MP treatments modified carbon and nitrogen cycling pathways, with PS1005 enhancing methanogenesis genes (mcrABG) and PS1010 negatively affecting denitrification genes (nirK, nirS). This study provides evidence of the complex effects of PS-MPs on soil health and agroecosystem functioning, highlighting their potential to alter soil properties and microbial communities, thereby affecting plant growth.